Effect of the diaphragmatic myofascial release technique on flowmetry results in healthy university students: pilot test - Astudillo Ganora, Ignacio Alejandro.; Cea Ávila, Sebastián.; Arroyo Álvarez, Julián.; Márquez Muñoz, Rayen.; Briceño Latoche, Anthony. (Editorial Salud, Ciencia y Tecnologia, 2024)
Introduction: post-COVID motor and respiratory sequelae have become a public health problem for rehabilitation teams around the world. Diaphragmatic myofascial release may be a strategy to improve respiratory parameters measured with flowmetry. Objective: to determine the effect of diaphragmatic myofascial release on respiratory function measured with flowmetry in healthy university students. Method: quasi-experimental study of before and after design, 32 healthy subjects, divided into 15 men and 17 women, with an average age of 23,97 years, a basal flowmetry was performed, immediately diaphragmatic myofascial release was performed for 10 minutes in a supine position, and then, perform flowmetry after diaphragmatic release. Results: the flowmetry values pre and post diaphragmatic myofascial release showed different results, PEF (peak expiratory Flow) pre versus post, shows a statistically significant difference (p=0,04). Meanwhile, the FEV1 value (Forced expiratory volume in 1 second) showed a statistically non-significant difference (p=0,37). Conclusions: diaphragmatic myofascial release can be a manual strategy to improve lung capacity.
Efecto de la técnica de liberación miofascial diafragmática en los resultados de flujometría, en estudiantes sanos universitarios: prueba piloto
Keywords: Flujometría; Osteopathic manipulation; Diafragma (Anatomía); Síndromes del dolor miofascial